Los intereses tutelables y la dimensión de los perjuicios reparables en el Derecho francés de la responsabilidad civil extracontractual - Borghetti, Jean-Sebastién (2014)
In Tort Law, it is said that an individual mustrepair the damage he causes.  What is the extention of this maxim? Is this affirmation accurate? What is considered damage for Law?Jean-Sebastién Borghetti answers this and other questions as understood by French Law, seeking to delimit the French system of civil liability. In that sense, through this  article, the author proposes that not all affronts constitute a damage as understood by Law, and that not every damage can be repaired.